Upaya Pemerintah dan Masyarakat dalam Menyikapi Kegiatan Lembaga Dakwah Islam Indonesia (LDII) di Kota Pontianak - Fauziah Fauziah (The Pontianak State Institute of Islamic Studies, 2016)
One of the dakwa organizations which continues to grow with quite a large number of followers and spread in some parts of Indonesia is a religious school of the Indonesian Islamic Dakwa Organization (known as LDII), In West Kalimantan, especially in the city of Pontianak, the LDII is growing fast just as in the other areas. The religious activities indicate an attitude which is also exclusive, extreme and tends to blame the practice of the religious teachings outside of the congregation. The religious attitude of the LDII in Pontianak, has not led to rejection, but the spotlight and syndrome of refusal from some communities have started to emerge especially around the neighborhood of its preaching center. The purpose of this study are: 1) to describe the nature of LDII in Pontianak, 2) to describe the LDII doctrine and its application in public life in Pontianak., 3). to reveal the efforts of the government and the public in addressing the organizational activities of LDII in Pontianak The procedure used in this study was the approach of Case Study. The data sources consist of primary and secondary data sources. Data collection techniques used in case study were observation, in-depth interviews and analysis of documentation. The results of the study, as follows: (1) The LDII in the city of Pontianak has spread across several districts i.e. 11 (eleven) locations that serve as the gathering of the congregation of LDII. The places are equipped with mosques as a place of worship and boarding schools; the Government and the public are still in the process of monitoring and preventing conflict or disputes and violence between fellow Muslims or within the community; by studying the development of the Indonesian Islamic Dakwa Organization (LDII) in Pontianak, which in general is still under control, this research will be a major contribution to the government in making policies.